2007
DOI: 10.1016/j.ijforecast.2006.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Business and consumer expectations and macroeconomic forecasts

Abstract: Abstract:Business and consumer surveys have become an essential tool for gathering information about different economic variables. While the fast availability of the results and the wide range of variables covered made them very useful for monitoring the current status of the economy, there is no consensus on their utility for forecasting macroeconomic developments.The objective of the paper is to analyse the possibility of improving forecasts for selected macroeconomic variables for the euro area using the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 24 publications
4
60
0
1
Order By: Relevance
“…Balances have also been used as explanatory variables in economic models (Altug and Çakmakli 2016;Guizzardi and Stacchini 2015;Martinsen et al 2014;Ghonghadze and Lux 2012;Robinzonov et al 2012;Lui et al 2011aLui et al , 2011bSchmeling and Schrimpf 2011;Franses et al 2011;Klein and Özmucur 2010;Graff 2010;Claveria et al 2007;Abberger 2007;Mitchell et al 2005a;Hansson et al 2005;Mittnik and Zadrozny 2005;Batchelor and Dua 1998;Kauppi et al 1996;Parigi and Schlitzer 1995;Bergström 1995;Rahiala and Teräsvirta 1993;Biart and Praet 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Balances have also been used as explanatory variables in economic models (Altug and Çakmakli 2016;Guizzardi and Stacchini 2015;Martinsen et al 2014;Ghonghadze and Lux 2012;Robinzonov et al 2012;Lui et al 2011aLui et al , 2011bSchmeling and Schrimpf 2011;Franses et al 2011;Klein and Özmucur 2010;Graff 2010;Claveria et al 2007;Abberger 2007;Mitchell et al 2005a;Hansson et al 2005;Mittnik and Zadrozny 2005;Batchelor and Dua 1998;Kauppi et al 1996;Parigi and Schlitzer 1995;Bergström 1995;Rahiala and Teräsvirta 1993;Biart and Praet 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Berk, 1999, Maag, 2010, and conclude that quantified qualitative survey expectations do not necessarily forecast the target variable better than simple time-series models (e.g. Claveria et al, 2007, Nolte and Pohlmeier, 2007, Breitung 2008, or directly suggested improvements and extensions of the CP approach to alleviate other problems of the method (e.g. Fishe and Lahiri, 1982, Löffler, 1999, Mitchell et al, 2007, or Müller, 2010.…”
Section: Related Literaturementioning
confidence: 99%
“…Firms may want to fill a vacancy, but are not able to get suitable candidates due to their low matching efficiency, for instance. Fourthly, a discussion of the aggregation of firm's responses, e.g., balances, exists in the literature (Croux/Dekimpe/Lemmens, 2005;Claveria/Pons/Ramos, 2007). Alongside this discussion of the sheer aggregation of the raw data, several methods exist to transform qualitative indicators into quantitative information.…”
Section: Cw-tesmentioning
confidence: 99%
“…Alongside this discussion of the sheer aggregation of the raw data, several methods exist to transform qualitative indicators into quantitative information. Rather than using the direction of employment change, a quantitative measure extracted from employment expectations may have predictive power for the magnitude of employment change (Claveria/Pons/Ramos, 2007). However, our paper gives initial insights into the forecasting performance of survey-based indicators for predicting labor market variables.…”
Section: Cw-tesmentioning
confidence: 99%
See 1 more Smart Citation